2006
DOI: 10.7326/0003-4819-145-12-200612190-00004
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Colonoscopy in an Integrated Health Care Delivery System

Abstract: Colonoscopy with biopsy or polypectomy is associated with increased risk for complications. Perforation may also occur during colonoscopies without biopsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
367
4
13

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 521 publications
(395 citation statements)
references
References 25 publications
11
367
4
13
Order By: Relevance
“…6 Gastrointestinal bleeding has also been reported as the most prevalent complication in adult studies. 7 Adult studies have also reported that older age is a risk factor for gastrointestinal bleeding, 7,9 In this study, the higher complication rate associated with younger age can be largely accounted for by bleeding complications. Our regression analysis showed that younger age was an independent predictor of bleeding-related complications, and 71% (24/34) of bleeding events in our cohort were reported in children younger than 10 years of age.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…6 Gastrointestinal bleeding has also been reported as the most prevalent complication in adult studies. 7 Adult studies have also reported that older age is a risk factor for gastrointestinal bleeding, 7,9 In this study, the higher complication rate associated with younger age can be largely accounted for by bleeding complications. Our regression analysis showed that younger age was an independent predictor of bleeding-related complications, and 71% (24/34) of bleeding events in our cohort were reported in children younger than 10 years of age.…”
Section: Discussionmentioning
confidence: 66%
“…The rate of perforation in adult colonoscopies is also very low, estimated at less than 0.2% (range, 0.03%-0.81%). 4,8,9,19,26 Overall, adult studies did not demonstrate a clear association between polypectomy and the rate of perforation. 6 Predisposing factors to perforations included the presence of adhesions, strictures, or severe diverticular disease; these conditions are less common in pediatrics.…”
mentioning
confidence: 99%
“…There were also 4.8 occurrences of postprocedure bleeding per 1000 colonoscopies that included biopsy or polypectomy. 43 In conclusion, in a large community-based U.S. population across multiple medical centers, physicians' adenoma detection rates were inversely related to the risk of interval colorectal cancer, including advanced-stage cancer and fatal interval colorectal cancer, among patients with up to 10 years of follow-up. This association was approximately linear across quintiles of adenoma detection rates in our population and was observed for male and female patients, cancers in the proximal and distal colon, and early and delayed interval cancers.…”
Section: Discussionmentioning
confidence: 99%
“…However, colonoscopy is an invasive procedure and carries with it an inherent risk, although the risk is low. Studies reported an overall complication rate of 2.9-5 per 1000 endoscopies and a perforation rate of 0.9-1.8 per 1000 endoscopies [42,43]. A screening colonoscopy program also reported a complication rate of 0.1% [44].…”
Section: Colon Examinations Colonoscopymentioning
confidence: 99%